Association of galectin-3 with changes in left ventricular function in recent-onset dilated cardiomyopathy. (3rd October 2019) - Rieth, Andreas J.; Jung, Claudia; Gall, Henning; Rolf, Andreas; Mitrovic, Veselin; Hamm, Christian W.; Sperzel, Johannes; Liebetrau, Christoph
Abstract: Background: The course of newly diagnosed dilated cardiomyopathy (DCM) varies from persistent reduction of left ventricular ejection fraction (LVEF) to recovery or even worsening. The aim of the present study was to examine the prognostic value of selected biomarkers with regard to changes in LVEF. Methods: Main inclusion criterion was LVEF ≤45% with exclusion of coronary artery or valvular heart disease. The primary endpoint was LVEF ≤35% in the follow-up echocardiogram. Galectin-3, N-terminal prohormone of brain natriuretic peptide (NT-proBNP) and C-reactive protein (CRP) were related to the endpoint. Results: Data from 80 DCM patients (55 male, mean age 53 years) were analyzed. Median LVEF was 25% (IQR 25–30). The endpoint was met for 24 patients (30%). These had higher baseline levels of galectin-3 (median 20.3 ng/mL [IQR 14.3–26.9] vs. 14.7 ng/mL [IQR 10.9–17.7], p = 0.007) and NT-proBNP (3089 pg/mL [IQR 1731–6694] vs. 1498 pg/mL [IQR 775–3890]; p = 0.004) in univariate Cox regression analysis. ROC analysis revealed that CRP (median 0.4 mg/dL [IQR 0.2–1.2]) was also related to the endpoint ( p = 0.043). Conclusion: Higher levels of galectin-3, NT-proBNP, and CRP were associated with LVEF ≤35% in our cohort. An approach utilizing a combination of biomarkers for patient management should be assessed in further studies.